Aspek – Aspek Psikologis dalam Tradisi “Nyumbang” Masyarakat Suku Jawa - Ayuwandani, Yosinta; Marselius Sampe Tondok (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
In the context of Indonesia's multicultural society, in the Javanese community, there exists the tradition of "Nyumbang," which is an integral part of Javanese life with rich cultural values. In the context of a collectivist society, the "Nyumbang" tradition encompasses psychological aspects that have not been explored in previous research. Therefore, this study aims to explore and elucidate the psychological aspects of the "Nyumbang" tradition in the Javanese community. This research employed a literature review method by conducting a search and analysis of relevant articles related to the "Nyambung" tradition. The researchers utilized pertinent theories in social psychology to unveil the psychological aspects contained within this tradition. This research found there are there main psychological aspects in the "Nyumbang” namely prosocial behavior, reciprocity, and collectivism. Events such as celebrations or weddings held by local people certainly require large costs. Based on this, there is a tradition of donating which aims to provide assistance to people who have needs. In this case, the material given in the tradition of donating can be in the form of money or in the form of materials. The conclusion obtained is that the psychological concept contained in the “Nyumbang” tradition is collectivism.